CONTRIBUTION OF MEDIA TECHNOLOGIES TO THE DEVELOPMENT OF STUDIES IN THE FIELD OF PHILOLOGY - Ade Kosasih; Tb. Ace Fahrullah; Uus Rustiman; Dwi Luthfiyani (Yayasan Education and Social Center, 2023)
Philology is a science that gets many contributions from various disciplines, including media technology. The purpose of this study is to uncover the contribution of media technology to the development of philological studies. Philological studies were carried out on ancient manuscripts containing handwritten texts, so they needed to be handled for their preservation. The existence of media technology is very helpful in efforts to preserve ancient manuscripts to be read and studied by current and future generations. This research uses a descriptive method by searching for data to be analyzed in accordance with phenomena that occur in society related to perceptions of philological science. The data recorded are in the form of social events that generally show a lack of attention to philology and manuscripts left by ancestors as cultural heritage. The results showed that there was still a low public understanding of philology. So to arouse attention to philology and manuscripts as cultural heritage, philology really needs other fields of science, especially media technology. Along with the development of technology, the ease of accessing various manuscripts can be done through the internet media. Nowadays, there are many websites that provide manuscript documents found in various museums and libraries. In that regard, media technology plays a very important role in the development of the field of philology through the transfer of media from various manuscripts to be read and studied by current and future generations. It proves that media technology contributed greatly to the development of studies in the field of philology